2014
DOI: 10.1097/hjh.0000000000000264
|View full text |Cite
|
Sign up to set email alerts
|

Aortic root diameter and risk of cardiovascular events in a general population

Abstract: Our results for the first time show that ARD indexed to height is predictive of incident nonfatal and fatal cardiovascular events among middle-aged individuals in the community and support the view that assessment of ARD in addition to left ventricular mass may refine cardiovascular risk stratification and preventive strategies in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 39 publications
3
73
1
Order By: Relevance
“…AoD indexed to BSA has been recommended in the current American Society of Echocardiography and European Association of Echocardiography guidelines 28. However, in several previous cross‐sectional and longitudinal studies, height was the most important determinant of AoD and therefore was regarded as more appropriate to normalize AoD 1, 10, 11. In the cross‐sectional analysis of the current study, height and BSA were significantly correlated with AoD, but both correlations were modest.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…AoD indexed to BSA has been recommended in the current American Society of Echocardiography and European Association of Echocardiography guidelines 28. However, in several previous cross‐sectional and longitudinal studies, height was the most important determinant of AoD and therefore was regarded as more appropriate to normalize AoD 1, 10, 11. In the cross‐sectional analysis of the current study, height and BSA were significantly correlated with AoD, but both correlations were modest.…”
Section: Discussionmentioning
confidence: 60%
“…In the Cardiovascular Health Study, a greater AoD was associated with a higher incidence of several cardiovascular events, including incident HF, stroke, cardiovascular mortality, and all‐cause mortality 9. In the Pamela study, a larger AoD indexed to height, but not absolute AoD or AoD indexed to BSA, was associated with cardiovascular events 11. In the Framingham Heart Study, a larger AoD was associated with incident HF 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some data, although not unanimous, that seem to support the concept that in hypertensive patients aortic root dilatation may represent an index of target organ damage, paralleling markers of well documented prognostic value such as left ventricular (LV) hypertrophy (LVH), carotid atherosclerosis and microalbuminuria [5][6][7][8][9][10][11][12][13][14]. Recent population-based studies showed that an enlarged ARD might predict an adverse prognosis, even in absence of aneurysmatic alterations [15][16][17][18].…”
Section: Introductionmentioning
confidence: 91%
“…In 6,483 participants to Framingham Heart Study, followed-up over an 8-year period, the risk of incident heart failure progressively increased with baseline ARD values [41]; the association of ARD with incident heart failure, however, lost statistical significance after adjustment for LV mass. In the PAMELA population, the adjusted risk for non-fatal and fatal cardiovascular events in subjects with both LVH and ARD was three-fold higher (HR = 2.8, 95 % CI 1.6-5.1, p \ 0.0005) than in reference group and much higher than in subjects with isolated LVH (HR = 1.9, 95 % CI 1.2-2.9, p = 0.003) [42]. Overall, these findings point towards an adverse prognostic significance of ARD even the absence of aneurysmatic aortic disease.…”
Section: Left Atrium Enlargementmentioning
confidence: 83%